Analisis Capaian Kinerja Pelaksanaan Anggaran Penerapan Aplikasi Electronic Monitoring Pelaksanaan Anggaran (e-MPA) - Atikah Rosalinda; Rindu Rika Gamayuni (Jurnal Akuntansi dan Keuangan (JAK), 2018)
This study aim to examine and found the empirical evidence the consistancy between budget absorption and realization after the implementation of Electronic Monitoring Budget Execution aplication (e-MPA) at Ministry of Religion working unit at Lampung Province. This study use 4.416 population data for the period of 2012 until 2013 before the implementation of e-MPA aplication and the period of 2015 until 2016 after the implementation of e-MPA aplication. Data used are secondary data obtained by accessing the site http://www.kemenag.go.id. The data analyzed using differentiation test with statistical test tool SPSS 22. The result shows that there is a difference of consistancy of budget absorption and there is also a difference on budget realization after the implementation of e-MPA aplication.the difference occured is the decreasing on statistic result of absorption consistancy and absorption realization for budgeting that indicates there is no goal congruence caused by communication pattern, information support, and uncorrect guidelines comprehension for e-MPA aplication.